IMPLEMENTATION OF ACTIONING CHILDREN AS VICTIMS OF SEXUAL VIOLENCE IN PANDEMIC SITUATIONS CORONAVIRUS DISEASE 2019 (COVID-19) - R. Ahmad Faisal Ramadhan; Mas Anienda Tien (JOSAR (Journal of Students Academic Research), 2022)
Sexual violence in the context of the COVID-19 pandemic has greatly increased. This is certainly very threatening the existence of the child. The purpose of this study was to determine the factors that cause children to become victims of sexual violence and to take action against children as victims of sexual violence in the COVID-19 pandemic situation. This research method uses empirical juridical. Data collection is done by literature study and interviews. Data analysis used descriptive analytical method with a qualitative approach. The results of this study indicate that the cause of the increase in children as victims of sexual violence in the Covid-19 pandemic situation is because the implementation of the action still does not provide preventive and repressive protection. Victims and families of victims of sexual violence who are unable to report and do not know how to report the procedure for sexual violence experienced by the child, victims of sexual violence against children who often do not provide information openly, lack of facilities and infrastructure as well as human resources in regional institutions, are the obstacles found. Thus, there is a need for socialization and new innovations to the community, as well as the allocation of funds to regional institutions to maximize prevention and prosecution of children as victims of sexual violence in the COVID-19 pandemic situation.